(عصرِ حاضر کے سماجی و اخلاقی چیلنجز اور ان کا قرآنی حل (مفتی محمد طاہر مسعود کی تفسیر فہم القرآن کا تنقیدی جائزہ : Contemporary Social & Moral Challenges & Their Qur’anic Solutions (A Critical Study of Tafsir Fehm-ul-Quran by Mufti Muhammad Tahir Masood) - Sadia Noreen,; Dr. Faizan Hassan Javed, (Al-Amīr Research Journal for Islamic Studies, 2025)
In the face of growing moral confusion, ideological unrest, and societal disintegration, contemporary Muslims are grappling with profound spiritual and ethical challenges. The erosion of Islamic values, rise of materialism, neglect of religious obligations, and misguidance of youth have contributed to a crisis of identity within the Ummah. In this context, the Qur’an remains a timeless source of divine guidance — offering comprehensive solutions to modern-day problems. Tafsir Fehm-ul-Quran by Mufti Muhammad Tahir Masood emerges as a significant scholarly contribution that reaffirms the relevance of Quranic teachings in today’s world. This study critically examines how Fehm-ul-Quran addresses contemporary social, moral, and ideological issues by providing spiritually grounded and practically applicable interpretations of the Qur’an. Mufti Tahir Masood’s approach blends classical exegetical tradition with modern realities, offering insight into pressing challenges such as ethical decay, breakdown of the family unit, loss of spiritual direction, economic disparity, injustice, and the influence of secular ideologies. His commentary highlights the Qur’an’s emphasis on justice, brotherhood, accountability, divine purpose, and human dignity. The research finds that Fehm-ul-Quran is not merely a work of traditional exegesis, but a dynamic tool for moral and social reform. By reinforcing the concept of purposeful human creation — rooted in worship and obedience to Allah — the tafsir serves as a reminder of the path to collective uplift and individual salvation. The study concludes that returning to the Qur’anic worldview, as interpreted in Fehm-ul-Quran, can help Muslims reclaim their moral compass and navigate the complexities of modern life with faith, clarity, and resilience. keywords: Tafsir Fehm-ul-Quran, Mufti Tahir Masood, Quranic exegesis, contemporary issues, Islamic ethics, moral reform, spiritual revival, social justice, modern challenges, Islamic worldview.